Regulatory considerations for vaccine development: talk 2 – clinical regulatory considerations 1 - Schrager, Lewis K. (Henry Stewart Talks, 2015)
Investigational New Drug (IND) regulations, Key clinical development milestones, Safety and efficacy concepts: a regulator’s perspective